30th Annual International Computer Software and Applications Conference: COMPSAC '06 : proceedings, 17-21 September 2006, Chicago, Illinois - Ceballos, Silvia (IEEE Computer Society, 2006)
V. 1. Regular papers/ Panels -- V. 2. Short papers/ Workshops/ Fast abstracts/ Doctoral Symposium
"IEEE Computer Society Order Number P2655"--Title page verso. - Includes bibliographical references and index
Includes bibliographical references and index
Parallel als Buch-Ausg. erschienen
Keywords: Konferenzschrift -- 17.09.2006-21.09.2006 -- Chicago, Illinois